Device and process for preparing long-durability thermal barrier coating through flash sintering
Through flash sintering process and device, the degradation and expansion of the thermal barrier coating in high temperature environment is solved, its durability and thermal insulation effect are improved, the densification and adhesion of the ceramic layer are enhanced, and the coating is ensured. stability and efficient performance.
Patent Information
- Application Number
- CN202411256225.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
Thermal barrier coatings are prone to degradation, expansion and contraction in high temperature environments, resulting in stress cracking, porosity closure reduces heat insulation ability, and manufacturing consistency is difficult to control, affecting its durability and performance.
Using flash sintering process and device, external electric field is applied through high-temperature furnaces and electrode wires, temperature distribution and microstructure are controlled, the porosity of the ceramic layer is reduced, hardness and fracture toughness are improved, and adhesion is enhanced by combining YSZ thermal barrier coating and platinum slurry layer. .
It significantly improves the durability and thermal insulation effect of the thermal barrier coating, extends its service life, reduces oxidation rate and stress concentration, and ensures the consistency and performance stability of the coating.
Smart Images

Figure CN119121116A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of aerospace technology, and in particular to a device and a process for preparing a long-durability thermal barrier coating by flash sintering. Background Art
[0002] Thermal barrier coatings (TBCs) are advanced material systems that are typically applied to metal surfaces operating at high temperatures, such as gas turbine or aerospace engine components, to isolate the components from the enormous and sustained heat loads. By doing so, these coatings significantly increase the efficiency and service life of engine components.
[0003] Despite their significant advantages, TBCs also face various concerns and challenges. First, TBCs degrade over time due to exposure to high temperatures, oxidation, and hot corrosion. The life of these coatings is a significant issue, especially as modern engines pursue higher efficiency, resulting in increasingly higher operating temperatures.
[0004] Secondly, engines often experience thermal cycles from ambient to high temperatures during takeoff and landing. This causes the TBC to expand and contract, which can cause stress in the coating and may crack or peel off. In addition, TBCs are typically brittle ceramic coatings with poor strain tolerance, which can cause the coating to crack and eventually fail under thermal or mechanical strain.
[0005] At high temperatures, the porosity of TBCs closes due to sintering, which reduces their thermal insulation capabilities and increases thermal conductivity. Some TBC materials undergo phase changes at high temperatures, resulting in volume changes and subsequent degradation of the coating. For components exposed to corrosive environments of high-temperature water, oxygen, or low-melting-point oxides, TBCs must not only meet thermal insulation requirements but also provide corrosion protection.
[0006] In addition, the bonding layer can be oxidized by oxygen diffused through the pores or cracks of the ceramic layer, forming thermally grown oxide (TGO), which affects TBC adhesion and may cause peeling. Manufacturing consistency is also an important issue, and the TBC application process requires careful control and consistency to ensure the quality and performance of the TBC. Summary of the invention
[0007] In view of the above-mentioned deficiencies in the prior art, the present invention provides a flash sintering device and process for a long-durability thermal barrier coating, which can significantly reduce the porosity of the ceramic layer of the thermal barrier coating, improve the hardness and fracture toughness, and help improve the durability of the thermal barrier coating.
[0008] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is: a device for preparing a long-durability thermal barrier coating by flash sintering, comprising a high-temperature furnace and a power supply connected to the high-temperature furnace;
[0009] The high temperature furnace comprises a shell and a furnace door arranged on the shell, the shell comprises a first shell and a second shell arranged adjacent to each other, an air cooling circulation system is arranged between the first shell and the second shell, a heating element is arranged inside the second shell, and a high temperature alumina coating is arranged on the inner wall of the second shell;
[0010] A hole is arranged on the top of the shell, the hole runs through the first shell and the second shell, a high-temperature electrode wire for applying an external electric field to the sample is arranged in the hole, and a programmable DC power supply and a multimeter are arranged at one end of the high-temperature electrode wire away from the hole.
[0011] The beneficial effects of the present invention are as follows: the device effectively controls the temperature distribution inside the high-temperature furnace through the adjacently arranged first shell and second shell and the air-cooling circulation system, which can avoid excessive thermal stress of the thermal barrier coating in a high-temperature environment and improve the durability of the thermal barrier coating; by arranging holes on the top of the shell, and arranging high-temperature electrode wires and external electric field application equipment in the holes, an external electric field can be applied to the sample, which can change the microstructure and performance of the thermal barrier coating, and further improve its durability and thermal barrier effect. By arranging a programmable DC power supply and a multimeter at one end of the high-temperature electrode wire away from the hole, the application conditions of the external electric field can be accurately controlled, and the electrical properties of the sample can be monitored in real time, so that the performance of the thermal barrier coating can be quantitatively analyzed and evaluated, providing a scientific basis for the optimal design of the thermal barrier coating.
[0012] Furthermore, the above-mentioned flash sintering device for long-durability thermal barrier coating has a safety limit switch and a protective door latch on the furnace door.
[0013] The beneficial effects of adopting the above further scheme are: the safety limit switch can monitor the position of the furnace door, and when the furnace door is not completely closed, it can promptly issue an alarm or stop the operation of the device to avoid accidents; the protective door latch can ensure that the furnace door remains firmly closed during operation to prevent the furnace door from opening accidentally, thereby protecting the safety of operators and equipment.
[0014] Furthermore, in the flash sintering device for the long-durability thermal barrier coating, the heating element is a silicon-molybdenum rod.
[0015] The beneficial effect of adopting the above further scheme is that the high temperature stability of the silicon-molybdenum rod can ensure that the device maintains a stable heating effect during long-term operation, thereby improving the sintering quality and production efficiency.
[0016] Furthermore, in the above-mentioned flash sintering device for long-durability thermal barrier coating, a temperature control instrument is provided on the outer wall of the first shell, a temperature sensor is provided on the inner wall of the second shell, and the temperature sensor and the temperature control instrument are electrically connected.
[0017] The beneficial effects of adopting the above further scheme are: the temperature control instrument can monitor and adjust the temperature of the device in real time to ensure that the temperature change can be accurately controlled during the sintering process; the electrical connection between the temperature control instrument and the temperature sensor can realize the automatic control function, that is, automatically adjust the heating power and time according to the set temperature range and process requirements.
[0018] Furthermore, the multimeter used in the flash sintering device for the long-durability thermal barrier coating is a UT61Epro multimeter.
[0019] The beneficial effect of adopting the above further scheme is that the UT61Epro multimeter can continuously measure 0-1000V voltage and 0-10A current for a long time, and can also use computer software to record the current and voltage data at a recording rate of 0.5s / time.
[0020] Furthermore, in the flash sintering device for the long-durability thermal barrier coating, the high-temperature electrode wire is a nickel alloy wire.
[0021] The beneficial effects of adopting the above further scheme are: when performing flash sintering treatment, it is necessary to select suitable high-temperature electrodes, which must meet the requirements of sintering materials and withstand the expected temperature and current conditions. The nickel-chrome alloy wire has excellent electrical conductivity at high temperatures and can resist oxidation and creep; at room temperature, the nickel-chrome alloy wire has sufficient flexibility to facilitate operation and processing.
[0022] Furthermore, the sintering process of the flash sintering device for the long-durability thermal barrier coating comprises the following steps:
[0023] S1: Arranging a YSZ thermal barrier coating on a metal substrate to obtain a YSZ thermal barrier coating sample;
[0024] S2: grinding the surface of the YSZ thermal barrier coating sample and setting a platinum slurry layer at both ends of the YSZ thermal barrier coating sample;
[0025] S3: Hang the treated YSZ thermal barrier coating sample inside the high temperature furnace through the high temperature electrode wire;
[0026] S4: Connect the electrodes of the high temperature electrode wire to the positive and negative terminals of the programmable DC power supply and connect to the circuit through a multimeter;
[0027] S5: Start the high temperature furnace. When the high temperature furnace reaches the preset temperature and remains stable for 5 minutes, turn on the programmable DC power supply.
[0028] S6: After the flash treatment is completed, turn off the equipment and let the YSZ thermal barrier coating sample cool naturally in the furnace.
[0029] Furthermore, in the flash sintering process of the long-durability thermal barrier coating, the size of the metal substrate is 20mmx10mmx3mm; the thickness of the YSZ thermal barrier coating is 300μm.
[0030] The beneficial effects of the present invention are as follows: the YSZ thermal barrier coating is a metal bonding layer and a surface ceramic layer. The metal bonding layer is located between the substrate and the ceramic layer, which plays a role in improving the adhesion and anti-oxidation of the ceramic layer, preventing the ceramic surface from peeling off prematurely. The double-layer material will also generate a thermally grown oxide layer between the ceramic layer and the bonding layer under high temperature conditions; as the flash treatment proceeds, the porosity of the ceramic layer decreases significantly, while the hardness and fracture toughness are continuously improved; the combined effect of the electric field and temperature field of the flash causes the grains in the ceramic layer to undergo local overheating of the grain boundaries, causing the grains to remelt and recrystallize. Blocky broken crystals of varying sizes are transformed into equiaxed grains with uniform interplanar spacing and large grain boundaries, and the size distribution of these equiaxed grains is relatively uniform. These equiaxed crystals help to improve the coating's resistance to fracture, and at the same time, this remelting and recrystallization behavior also helps to eliminate poor contact between grains, heal microcracks and pores generated by spraying, block the diffusion channels of oxygen elements, and reduce the oxidation rate. The flash firing treatment also causes a phase transformation of the ZrO2 in the ceramic layer. A small part of the m-ZrO2 is converted into t-ZrO2, and the volume does not expand on a large scale. This not only unifies the phase structure in the ceramic layer, but also the volume difference between the t-ZrO2 phase structure and the c-ZrO2 phase caused by the over-temperature sintering phase transformation is smaller than that of the m-ZrO2 phase and the c-ZrO2 phase. This helps to reduce the volume expansion of the ceramic layer during over-temperature sintering and slow down the size and rate of stress concentration in the layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the structure of a flash sintering device;
[0032] Figure 2 This is the grinding and polishing cross-sectional morphology of the sample after flash treatment;
[0033] Figure 3 This is the cross-sectional morphology of the sample after flash burning treatment;
[0034] Figure 4 TEM micrographs and SAED patterns of the YSZ ceramic layer before and after flash firing;
[0035] Figure 5 XRD results of YSZ ceramic layer before and after flash sintering;
[0036] Figure 6 The growth of TGO in the thermal barrier coating after treatment;
[0037] Figure 7 The change of macroscopic Young's modulus of thermal barrier coating after treatment;
[0038] Figure 8 The surface morphology of thermal barrier coatings in thermal cycle experiments before and after flash treatment;
[0039] Fig. 9 The cross-sectional morphology of thermal barrier coating thermal cycle test before and after flash treatment;
[0040] Fig.10 is the high temperature oxidation failure probability curve of the treated thermal barrier coating;
[0041] Fig.11 is the sintering failure probability curve of the thermal barrier coating after treatment;
[0042] Among them: 1. Shell; 2. Furnace door; 3. First shell; 4. Second shell; 5. Heating element; 6. Hole; 7. High-temperature electrode wire; 8. Programmable DC power supply; 9. Multimeter; 10. Safety limit switch; 11. Protective latch; 12. Temperature control instrument. DETAILED DESCRIPTION
[0043] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0044] like Figure 1 As shown, this embodiment provides a device for preparing a long-durability thermal barrier coating by flash sintering, comprising a high-temperature furnace and a power supply connected to the high-temperature furnace;
[0045] The high temperature furnace includes a shell 1 and a furnace door 2 arranged on the shell 1, and a safety limit switch 10 and a protective latch 11 are arranged on the furnace door 2. The shell 1 includes a first shell 3 and a second shell 4 arranged adjacent to each other, and an air cooling circulation system is arranged between the first shell 3 and the second shell 4. A heating element 5 is arranged inside the second shell 4, and the heating element 5 is a silicon molybdenum rod. A high-temperature alumina coating is arranged on the inner wall of the second shell 4; a temperature control instrument 12 is arranged on the outer wall of the first shell 3, and a temperature sensor is arranged on the inner wall of the second shell 4, and the temperature sensor and the temperature control instrument 12 are electrically connected. The electrical connection between the temperature control instrument 12 and the temperature sensor can realize the automatic control function, that is, automatically adjust the heating power and time according to the set temperature range and process requirements.
[0046] A hole 6 is provided on the top of the shell 1, and the hole 6 runs through the first shell 3 and the second shell 4. A high-temperature electrode wire 7 for applying an external electric field to the sample is provided in the hole 6, and the high-temperature electrode wire 7 is a nickel-chrome alloy wire. A programmable DC power supply 8 and a multimeter 9 are provided at one end of the high-temperature electrode wire 7 away from the hole 6. The multimeter 9 is a UT61Epro multimeter, which can continuously measure 0-1000V voltage and 0-10A current for a long time, and can also use computer software to record current and voltage data, with a recording rate of 0.5s / time. The programmable DC power supply 8 is specifically a IT-M3900D-300-20 high-power programmable DC power supply, the voltage can be adjusted within 0-300V, the display accuracy is 0.01V, and the current can be adjusted within 0-20A, and the display accuracy is 1mA. It is mainly used to provide an external electric field for the flash burning process to achieve rapid and dense sintering of materials.
[0047] The sintering process of the flash sintering device for the long-durability thermal barrier coating comprises the following steps:
[0048] S1: a YSZ thermal barrier coating is provided on a metal substrate, specifically, a YSZ thermal barrier coating is deposited on a nickel-based alloy substrate by plasma spraying technology to obtain a YSZ thermal barrier coating sample, wherein the size of the metal substrate is 20 mm x 10 mm x 3 mm, and the thickness of the YSZ thermal barrier coating is 300 μm.
[0049] S2: grinding the surface of the YSZ thermal barrier coating sample and setting a platinum slurry layer at both ends of the YSZ thermal barrier coating sample;
[0050] S3: Hang the processed YSZ thermal barrier coating sample inside the high-temperature furnace through the high-temperature electrode wire 7.
[0051] S4: Connect the electrodes of the high temperature electrode wire 7 to the positive and negative terminals of the programmable DC power supply 8, and connect to the circuit through the multimeter 9;
[0052] S5: Start the high temperature furnace. When the high temperature furnace reaches a predetermined temperature and remains stable for 5 minutes, turn on the programmable DC power supply 8;
[0053] S6: After the flash treatment is completed, turn off the equipment and let the YSZ thermal barrier coating sample cool naturally in the furnace.
[0054] The factors affecting flash burning are: electric field strength (V / cm), current density (mA / mm2), holding time (s) and furnace temperature (℃). The higher the electric field strength, the shorter the required furnace temperature and holding time, and the current density mainly affects the density of the sample. In this embodiment, the electric field strength is selected, from which the holding time and furnace temperature can be determined, and then 5 different current density values are selected to obtain thermal barrier coating samples with different densities. The specific flash treatment process parameters are shown in Table 1.
[0055] Table 1: Flash treatment process parameters
[0056]
[0057] Metallographic specimens were prepared for the flash-sintered samples, and the cross-sectional morphology and fracture morphology were analyzed.
[0058] like Figure 2 As shown, it is the initial morphology of the thermal barrier coating after spraying. It can be observed that there are numerous tiny microcracks and spherical pores with a diameter of about 1-5μm, and some pores intersect with the microcracks. Figure 2 (b) is after 20mA / mm 2 From the microscopic morphology after current density flash treatment, it can be found that some microcracks are healed in the middle, the crack length begins to decrease, and the pores remain basically unchanged. Figure 2 (c) The displayed value is 40 mA / mm 2 The morphology after current density flash treatment shows that the microcracks have not changed, but the number and size of pores have decreased. Figure 2 (d) is after 60mA / mm 2 The morphology after current density flash treatment, at this time the number and size of microcracks in the ceramic layer are much smaller than Figure 2 (a) Initial morphology, the pore size is also getting smaller. Figure 2 It can be observed in (e) and (f) that after 80 and 100 mA / mm 2 After current density flash treatment, the size and number of microcracks have been basically fixed. Although they are much smaller than the initial morphology, the increase in current density has not brought a greater impact; while the size and number of pores have been decreasing, and the shape is gradually changing from the initial nearly spherical shape to an irregular shape.
[0059] Figure 3 Shown are the cross-sectional microstructures of the samples before and after flash sintering treatment. Figure 3 (a) is the initial morphology of the thermal barrier coating after spraying. It can be observed that the ceramic layer of the thermal barrier coating after spraying is enriched in fine and large-sized block particles. Figure 3 From (b) to (d), as the current density gradually increases, it can be found that most of the fine particles have merged into strips, and the size is increasing. Some areas have become hardened and appear plate-like. Figure 3 In (e), it can be observed that the strips and plates are fused, the previously existing large pores are transformed into small pores, and the entire ceramic layer presents a unified plate shape. When the current density increases to the maximum value, Figure 3 (f) The cross-sectional morphology is completely different from that of the sprayed state. The entire ceramic layer has become a flat plate composed of multiple plates, with some small pores scattered on it, with various sizes and shapes.
[0060] TEM and XRD tests were performed on the samples before and after flashing. First, the cylindrical samples were mounted in a stainless steel tube with an inner diameter of 16 mm with epoxy resin, and then a 1 mm thick slice was cut along the normal direction of the coating surface. The slice was then fixed on a tripod polisher with epoxy resin, thinned mechanically, and polished from both sides until the ceramic coating became transparent. Finally, a low-angle ion polisher was used to further thin the sample thickness. The samples containing the ceramic layer were examined and analyzed using a FEITALOS F200XG2 transmission electron microscope equipped with a qualitative microanalysis device. The XRD sample was prepared using a ceramic layer bulk material, and a Bruker D8 Advance X-ray diffractometer (XRD) was used to measure and analyze the physical phase. The diffraction source was Cu target Ka rays, the scanning speed was 2° / min, and the scanning range was 20°-80°.
[0061] like Figure 4 Shown are TEM micrographs and SAED patterns of the YSZ ceramic layer before and after flash firing; Figure 4 (a) is the cross-sectional morphology of the sprayed ceramic layer; Figure 4 (b) SAED diffraction calibration of the sprayed ceramic layer; Figure 4 (c) is the lattice spacing of the sprayed ceramic layer; Figure 4 (d) is the cross-sectional morphology of the flash-sintered ceramic layer; Figure 4 (e) SAED calibration of the flash-sintered ceramic layer; Figure 4 (f) is the lattice spacing of the flash-fired ceramic layer.
[0062] like Figure 5 As shown, the XRD test results of the ceramic layer before and after flash burning show that there are two phase structures of m-ZrO2 and t-ZrO2 in the sprayed thermal barrier coating ceramic layer, while after flash burning, the thermal barrier coating has only t-ZrO2 structure in its ceramic layer, and the phase structure is stable.
[0063] The plasma sprayed ceramic layer presents a flat building block structure with a flaky structure, some cracks and pores, and some columnar grains in some flat blocks. By using TEM, it can be found that the pores and microcracks in the ceramic layer are mainly caused by poor contact between the bulk grains. In the ceramic layer after flash treatment, it can be observed that the ceramic layer has been transformed into a large grain boundary planar structure composed of a series of small equiaxed grains with a size between 0.1 and 0.6μm. The flash treatment causes the crystal plane of the ceramic layer to change, the arrangement is more orderly, and the crystal plane spacing has changed from two spacings, one large and one small, to a uniform spacing.
[0064] Table 2: Porosity and mechanical properties of the ceramic layer before and after flash sintering
[0065]
[0066] In order to further analyze the effect of flash sintering on the performance of the ceramic layer, the porosity and mechanical properties of the samples were tested, and the results are shown in Table 2. It can be found that with the progress of flash sintering, the porosity of the ceramic layer is greatly reduced, while the hardness and fracture toughness are continuously improved.
[0067] Based on all the above morphology and composition test results, it can be considered that the combined effect of the electric field and temperature field of the flash burning caused the grains in the ceramic layer to be locally overheated at the grain boundaries, causing the grains to remelt and recrystallize. Blocky crystals of varying sizes have become equiaxed grains with uniform interplanar spacing and large grain boundaries, and the size distribution of these equiaxed grains is relatively uniform. These equiaxed crystals help to improve the fracture resistance of the coating. At the same time, this remelting and recrystallization behavior also helps to eliminate poor contact between grains, heal microcracks and pores generated by spraying, block the diffusion channel of oxygen elements, and reduce the oxidation rate. The flash firing treatment also causes a phase transformation of the ZrO2 in the ceramic layer. A small part of the m-ZrO2 is converted into t-ZrO2, and the volume does not expand on a large scale. This not only unifies the phase structure in the ceramic layer, but also the volume difference between the t-ZrO2 phase structure and the c-ZrO2 phase caused by the over-temperature sintering phase transformation is smaller than that of the m-ZrO2 phase and the c-ZrO2 phase. This helps to reduce the volume expansion of the ceramic layer during over-temperature sintering and slow down the size and rate of stress concentration in the layer.
[0068] In order to further verify the optimization effect of the durability of the thermal barrier coating, the F-5 group of samples with the best flash treatment effect were selected for high-temperature oxidation and high-temperature sintering. At the same time, in order to eliminate the accidental, referring to the flash treatment process of the F-5 group, ten groups of flash samples were prepared again and their porosity and mechanical properties were measured to ensure the accuracy of the experimental results.
[0069] Table 3: Porosity and mechanical properties of the ceramic layer after flash sintering
[0070]
[0071] It can be seen from Table 3 that the flash sintering process of group F-5 is relatively stable, and the porosity and mechanical properties of the optimized thermal barrier coatings of group 10 are similar to those of group F-5 samples, which once again verifies the stability of the flash sintering process of the thermal barrier coating durability optimization technology used in this embodiment. Therefore, these 10 groups of treated samples were selected for high-temperature oxidation and high-temperature sintering treatments to obtain the changes in TGO growth parameters and macroscopic Young's modulus parameters, and the failure probabilities of high-temperature oxidation and sintering failures were calculated.
[0072] Isothermal high temperature oxidation experiment: The samples were subjected to isothermal high temperature load by heating in a high temperature furnace. The furnace temperature was set at 900℃, 1000℃, 1100℃ and 1200℃, and maintained for 0, 5, 10, 20, 50, 100, 150, 200, 300 and 500h respectively. Then the samples were taken out and metallographic specimens were made to measure the thickness of TGO.
[0073] High temperature sintering experiment: To explore the change of mechanical properties of ceramic layer with time under sintering effect, the disc sample was heat treated in high temperature furnace. Because YSZ has obvious sintering behavior above 1000℃, in order to fit the temperature relationship curve more conveniently, four cycle temperatures of 1000℃, 1100℃, 1200℃ and 1300℃ were set, with a heating rate of 10℃ / min, and the temperature was kept for 1, 2, 5, 10, 20, 50, 100, 200 and 500h respectively, and then the furnace was cooled, and the cooling rate was less than 2℃ / min to reduce the initiation and expansion of cracks in the coating.
[0074] like Figure 6-7 The following are the TGO growth and macroscopic Young's modulus changes of the samples treated by F-5 process at different temperatures and times. Figure 6 It can be seen that under the same experimental conditions, the growth rate of TGO at different temperatures of the thermal barrier coating sample after flash treatment tends to be slower than that of the sprayed thermal barrier coating, and the TGO thickness is also smaller than that of the sprayed thermal barrier coating, indicating that the densification of the ceramic layer caused by flash treatment can indeed block the oxygen diffusion channel and slow down the oxidation rate.
[0075] Figure 7 The change of macroscopic Young's modulus of the thermal barrier coating after flash treatment is shown. It can be observed that under the same experimental conditions, although the initial Young's modulus of the thermal barrier coating after flash treatment is higher than that of the sprayed thermal barrier coating, its growth rate and growth amount are smaller than those of the sprayed thermal barrier coating, and the growth rate and growth amount below 1200°C are reduced a lot. This result indicates that the densification of the ceramic layer improves the strain tolerance of the ceramic layer and the fracture resistance of the ceramic layer. The densification of the ceramic layer can effectively improve the strain tolerance of the ceramic layer, improve the fracture resistance of the ceramic layer, and also slow down the rate of high-temperature oxidation.
[0076] A thermal cycle experiment was conducted on the thermal barrier coating before and after flash treatment using a gas thermal shock comprehensive test bench. A thermal cycle was set as follows: the sample surface was heated to a preset temperature (about 60-90s) by a high-temperature flame flow; and the sample surface temperature was maintained at a preset temperature ±1°C (the time was set to 300s); then the sample surface was surface cooled to reduce the temperature to below 100°C (about 120s). During the entire experiment, the substrate was kept back-cooled with room temperature cold air (the back temperature was 200-400°C lower than the main temperature during insulation).
[0077] like Figure 8 and Fig. 9 As shown, in this experiment, each sample was subjected to 100 thermal cycles to observe the shedding area of the thermal barrier coating after the thermal cycles; Figure 8 This is the surface morphology of the sample after thermal cycling test. As can be seen from the figure, Figure 8 (a) shows that the sprayed thermal barrier coating has fallen off over a large area after 100 cycles, which is close to 40% of the entire surface. Figure 8 It can be observed from (b) to (f) that the thermal barrier coating that has undergone flash treatment has a very small peeling area after 100 cycles, with the largest one being close to 10%.
[0078] Fig. 9 This is the cross-sectional morphology after the thermal cycle experiment. Fig. 9 As can be seen in (a), the fracture crack of the sprayed thermal barrier coating is inclined along the thickness direction of the coating, and there is a large through-crack in the ceramic layer near the ceramic / bonding interface, which is parallel to the interface. Fig. 9 (b) shows that there are also many transverse and oblique cracks in the ceramic layer, which are not small in size. Fig. 9 In (c), the long cracks in the ceramic layer disappear, and are replaced by numerous small cracks and large pore defects. Fig. 9 (d)-(f), the number of microcracks also gradually decreases, the pore size continues to decrease, and the number remains basically unchanged.
[0079] The thermal cycling results show that the densification treatment of the ceramic layer can reduce initial defects such as microcracks and pores in the sprayed ceramic layer, delay the cracking time of the ceramic layer under external and internal stresses, and improve the damage strain tolerance of the ceramic layer, thereby effectively improving the thermal cycling life of the thermal barrier coating.
[0080] According to the TGO growth and Young's modulus after flash treatment, the failure probability of the thermal barrier coating under these two failure modes is calculated.
[0081] from Figure 6 The experimental fitting constant value required to fit the high temperature oxidation failure criterion formula is C = 345m / s 0.25 , Q = 61751 J / mol, n = 0.25, the failure probability is calculated using the Monte-Carlo calculation model, and the results are as follows Fig.10 shown.
[0082] Fig.10The figure shows the change of high-temperature oxidation failure probability of flash thermal barrier coating with time and temperature. Compared with the high-temperature oxidation failure probability curve of sprayed thermal barrier coating, the growth trend of the curve is basically the same at different temperatures, because it is the same failure mode. However, the growth rate has decreased, and the service life has increased. Taking the failure probability of 60% as the service life limit of thermal barrier coating, the service life of thermal barrier coating after flash treatment can reach 3580h in 1200℃ environment, while that of sprayed thermal barrier coating is only 1987h. When the ambient temperature is 1100℃, the service life of flash thermal barrier coating is 8253h, while that of sprayed thermal barrier coating is only 6878h. In 1000℃ environment, the service life of both reaches more than 10000h, but the growth rate of the flash curve is much lower than that of the sprayed state. It can be seen that the densification treatment of the ceramic layer effectively reduces the diffusion rate of oxygen elements, thereby reducing the high-temperature oxidation rate of the thermal barrier coating, enhancing the ability of the thermal barrier coating to resist high-temperature oxidation, and improving the durability of the thermal barrier coating to high-temperature oxidation.
[0083] like Fig.11 The figure shows the growth curve of the probability of sintering failure of the flash thermal barrier coating. The densification treatment of the ceramic layer effectively enhances the strain tolerance of the ceramic layer of the thermal barrier coating, improves the ability of the thermal barrier coating to resist fracture, and improves the durability of the thermal barrier coating to resist sintering failure.
[0084] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A device for preparing a long-durability thermal barrier coating by flash sintering, characterized in that: including a high temperature furnace and a power source connected to the high temperature furnace; The high-temperature furnace comprises a shell (1) and a furnace door (2) arranged on the shell (1); the shell (1) comprises a first shell (3) and a second shell (4) arranged adjacent to each other; an air cooling circulation system is arranged between the first shell (3) and the second shell (4); a heating element (5) is arranged inside the second shell (4); and a high-temperature aluminum oxide coating is arranged on the inner wall of the second shell (4); A hole (6) is arranged on the top of the shell (1), and the hole (6) passes through the first shell (3) and the second shell (4). A high-temperature electrode wire (7) for applying an external electric field to a sample is arranged in the hole (6), and a programmable DC power supply (8) and a multimeter (9) are arranged at one end of the high-temperature electrode wire (7) away from the hole (6).
2. The flash sintering device for long-durability thermal barrier coating according to claim 1, characterized in that: The furnace door (2) is provided with a safety limit switch (10) and a protective door latch (11).
3. The flash sintering device for long-durability thermal barrier coating according to claim 1, characterized in that: The heating element (5) is a silicon-molybdenum rod.
4. The flash sintering device for long-durability thermal barrier coating according to claim 1, characterized in that: A temperature control instrument (12) is arranged on the outer wall of the first shell (3), and a temperature sensor is arranged on the inner wall of the second shell (4); the temperature sensor and the temperature control instrument (12) are electrically connected.
5. The flash sintering device for long-durability thermal barrier coating according to claim 1, characterized in that: The multimeter (9) is a UT61Epro multimeter.
6. The flash sintering device for long-durability thermal barrier coating according to claim 1, characterized in that: The high temperature electrode wire (7) is a nickel alloy wire.
7. A sintering process of a flash sintering device for a long-durability thermal barrier coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: Arranging a YSZ thermal barrier coating on a metal substrate to obtain a YSZ thermal barrier coating sample; S2: grinding the surface of the YSZ thermal barrier coating sample and setting a platinum slurry layer at both ends of the YSZ thermal barrier coating sample; S3: Hanging the treated YSZ thermal barrier coating sample inside a high-temperature furnace through a high-temperature electrode wire (7); S4: connecting the electrodes of the high temperature electrode wire (7) to the positive and negative terminals of the programmable DC power supply (8), and connecting to the circuit via a multimeter (9); S5: Start the high temperature furnace. When the high temperature furnace reaches a predetermined temperature and remains stable for 5 minutes, turn on the programmable DC power supply (8); S6: After the flash treatment is completed, turn off the equipment and let the YSZ thermal barrier coating sample cool naturally in the furnace.
8. The flash sintering process of the long-durability thermal barrier coating according to claim 7, characterized in that: The size of the metal substrate is 20 mm x 10 mm x 3 mm; the thickness of the YSZ thermal barrier coating is 300 μm.
